The Structure-Phase State and Corrosion Resistance Modification of Austenitic Steel in Various Conditions Ion Implantation; 7 International conference on modification of materials with particle beams and plasma flows - Ovchinnikov S. V.; Tyumentsev A. N.; Korotaev A. D.; Nalesnik O. I. Oleg Ivanovich; Pinzhin Yu. P.; Nikolaev A. G.; Yushkov G. Yu. (Fundamentals of modification processes, 2004)
Title from the title-page.